2019
DOI: 10.3389/fpls.2019.01272
|View full text |Cite
|
Sign up to set email alerts
|

Structural Plasticity of Intrinsically Disordered LEA Proteins from Xerophyta schlechteri Provides Protection In Vitro and In Vivo

Abstract: Late embryogenesis abundant (LEA) proteins are essential to the ability of resurrection plants and orthodox seeds to protect the subcellular milieu against irreversible damage associated with desiccation. In this work, we investigated the structure and function of six LEA proteins expressed during desiccation in the monocot resurrection species Xerophyta schlechteri (XsLEAs). In silico analyses suggested that XsLEAs are hydrophilic proteins with variable intrinsically disordered protein (IDP) properties. Circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 118 publications
(169 reference statements)
1
20
0
Order By: Relevance
“…417 Multiple studies have demonstrated the ability of LEA proteins to protect biological entities such as proteins and membranes in desiccating environments. 400,[418][419][420][421][422] In one such study, Goyal et al reported that recombinant forms of AavLEA1, a group 3 LEA protein, can protect against desiccation induced aggregation of citrate synthase (CS), and helps retain its activity. 401 They hypothesized that owing to an unordered and flexible structure, LEA proteins can act as a molecular shield, thus forming a physical barrier to suppress any contact between CS molecules.…”
Section: Materials Advancesmentioning
confidence: 99%
“…417 Multiple studies have demonstrated the ability of LEA proteins to protect biological entities such as proteins and membranes in desiccating environments. 400,[418][419][420][421][422] In one such study, Goyal et al reported that recombinant forms of AavLEA1, a group 3 LEA protein, can protect against desiccation induced aggregation of citrate synthase (CS), and helps retain its activity. 401 They hypothesized that owing to an unordered and flexible structure, LEA proteins can act as a molecular shield, thus forming a physical barrier to suppress any contact between CS molecules.…”
Section: Materials Advancesmentioning
confidence: 99%
“…It may rely on the presence of particular minor VLCFAs such as 8,11,14eicosatrienoic acid (C20:3n6) and 4,7,10.13.16,19-docosahexaenoic acid (C22:6n3), which exhibited higher contents in H. plicatum than H. caudiculatum and others only detected in H. plicatum such as 13-docosenoic acid (C22:1n9) and 15-tetracosenoic acid (C24:1n9) fatty acids. Another alternative explanation besides this lipid profile, is the interaction of membranes with other biochemical membrane stabilizers such as the amphipathic LEA proteins or sugar-alcohols, such as those Plants 2019, 8, x; doi: FOR PEER REVIEW www.mdpi.com/journal/plants observed in Xerophyta schlechteri [47] or Pitcairnia burchellii [48]. It is likely that a more complex hypothesis should be invoked to explain our observations regarding differences in membrane stability observed between these two filmy ferns species ( Figure 2) contrasting in their desiccation tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…There is relatively little research on the protective roles of other groups, including the LEA_1 proteins, which are highly expressed in mature seeds and also accumulate in vegetative tissues under stress conditions [ 4 , 5 , 6 ]. Some genetic studies have been performed showing that the over-expression of LEA_1 genes, such as LEA4-1 from Brassica napus , BhLEA1 and BhLEA2 from Boea hygrometrica , AtLEA4-5 from Arabidopsis thaliana , and XsLEA1-8 from Xerophyta schlechteri , confer tolerance to salt, drought and osmotic stress in transgenic plants [ 5 , 6 , 7 ]. The over-expression of recombinant Gastrodia elata GeLEA1-1 or Xerophyta schlechteri XsLEA1-8 enhances Escherichia coli viability under low-temperature or heat stress [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some genetic studies have been performed showing that the over-expression of LEA_1 genes, such as LEA4-1 from Brassica napus , BhLEA1 and BhLEA2 from Boea hygrometrica , AtLEA4-5 from Arabidopsis thaliana , and XsLEA1-8 from Xerophyta schlechteri , confer tolerance to salt, drought and osmotic stress in transgenic plants [ 5 , 6 , 7 ]. The over-expression of recombinant Gastrodia elata GeLEA1-1 or Xerophyta schlechteri XsLEA1-8 enhances Escherichia coli viability under low-temperature or heat stress [ 7 , 8 ]. In addition, in vitro, the recombinant LEA_1 proteins AtLEA4-2 and AtLEA4-5 (both A. thaliana ) and XsLEA1-8 can preserve lactate dehydrogenase activity and prevent this enzyme aggregating during freeze鈥搕haw, heat, desiccation and oxidative stress [ 7 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation